Un Dia Na Vida de Uma Estrela . Divine Nubia - Mastro, Ricky (Mastro, Ricky ; Giasetti, Sarah, 2006)
Verzio FF submission A day in the life of Divine Nubia, a transexual in Rio aspiring to be a rich and famous star.